PERANCANGAN SISTEM INFORMASI PENERIMAAN SISWA BARU PADA SMA ISLAM PB. SOEDIRMAN 2 BEKASI BERBASIS WEB - Meilinda Santoso (2020)
Admission of new students is one of the processes in every school to screen selected prospective students according to the criteria prescribed by the school. In general, the process of admission of new students is done through the registration stage, follow several tests, and announcement of the results of student admission selection. SMA ISLAM PB. SOEDIRMAN 2 BEKASI was a high schoolin Bekasi Regency. In the implementation of new student admission activities are still done manually or have been computerized but using Microsoft Excel, which can allow some obstacles, such as lost or damaged forms and admins incorrectly input new prospective student data. It takes an information system that can help the process of receiving new students. With a new website- based admissions information system is expected to help facilitate in the process of receiving new students, such as data processing, fast and precise information delivery, and the announcement of the selection results are managed quickly. The method used is the prototype method. The result of this research is the information system in the SMA ISLAM PB. SOEDIRMAN 2 BEKASI is web-based. From this system is expected to produce information that is precise, fast and accurate.